Relation of reproductive disturbance in sheep and Leptospira interrogans serovar Icterohaemorrhagiae infection: Impacts on cellular oxidation status - da Silva A.S.* (2019)
© 2019 Elsevier LtdThis study evaluated the seropositivity of Brucella abortus and Leptospira interrogans in ewes with reproductive disturbances in southern Brazil and verified the creatine kinase (CK) activity and oxidation status via assessment of superoxide dismutase, glutathione peroxidase and glutathione transferase in serum of seropositive animals for L. interrogans serovar Icterohaemorrhagiae. For Leptospira infection 381 animals with clinical history of reproductive disturbance from Planalto Serrano de Santa Catarina (Brazil) were analyzed, showing an occurrence for L. interrogans of 20.2% from which 81.8% were seropositive for L. interrogans Icterohaemorrhagiae. Serovars Wolfii, Grippothyphosa, Bratislava, Canicola and Butembo were also identified. In the case of B. abortus, positive cases were identified by buffered acidified antigen, finding 14 positive samples, but none of them were positive after a second test (2-mercaptoethanol), showing the absence of relationship between infection with B. abortus and abortion in the tested individuals. Serum reactive oxygen species (ROS) levels and CK activity were found higher in animals positive for Leptospira infection, presenting higher titrations (1:320) than non-infected individuals. Serum glutathione peroxidase activity was higher in positive animals with titrations 1:160 and 1:320, while serum glutathione S-transferase was higher in positive individuals only for titrations 1:320. Serum superoxide dismutase showed lower activity in infected animals with titrations of 1:320. Our results show the region of Planalto Serrano de Santa Catarina with a high occurrence levels of sheep infected by L. interrogans serovar Icterohaemorrhagiae, from which animals with high titrations (1:320) present oxidative stress elicited by excessive ROS production, triggering the stimulation of antioxidant systems to counter this excess. In summary, ovine with higher titrations (1:320) present oxidative damage that can contribute to disease pathophysiology.